Digital Campaign: Character Branding and Framing towards the 2024 Presidential Election - Ahmad Zuhdi; Cecep Suryana; Rodon Pedrason; Satryo Sasono; Ahmad Musabiq Habibie (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
The existence of social media allows us to interact with anyone quickly and inexpensively. Political figures then use this as a medium in carrying out digital campaigns. This research was carried out to see how social media is used as a digital campaign tool by politicians to build a certain character or image in the eyes of society or the public. This research will be carried out using a qualitative approach and descriptive analysis. The data used in this study comes from the results of previous studies. The results of this study found that it is necessary to have a good brand or image from the public for the popularity of these politicians so that the implementation of digital campaigns can run effectively. Therefore, character-building needs to be done so that the digital campaign carried out to carry out the presidential election in the future can run well.